2019
DOI: 10.20343/teachlearninqu.7.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive Learning Communities: Transformative Spaces for Underprivileged, Underserved, and Historically Underrepresented Graduate Students at Their Institutions

Abstract: In this paper we propose a new vision of educational development that reimagines how graduate instructors are socialized and professionalized in academic settings. We describe a Transgressive Learning Community (TLC) that empowers graduate instructors with tools to reveal, mitigate, and disrupt oppressive structures in higher education. Our learning community is founded on critical race and feminist conceptualizations of pedagogical inquiry in its design, implementation, and assessment to serve underprivileged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Incorporating scholarship of teaching and learning into graduate level courses also helps promote reflective practices and collaboration between faculty and graduate students (Auten and Twigg 2015). These communities have shown more long-term effectiveness than one-time teaching workshops and other short-term trainings (Drane et al 2019).…”
Section: Pedagogical Influencementioning
confidence: 99%
See 3 more Smart Citations
“…Incorporating scholarship of teaching and learning into graduate level courses also helps promote reflective practices and collaboration between faculty and graduate students (Auten and Twigg 2015). These communities have shown more long-term effectiveness than one-time teaching workshops and other short-term trainings (Drane et al 2019).…”
Section: Pedagogical Influencementioning
confidence: 99%
“…We do this to do our small part in dismantling current systems of marginalization and oppression within commonly used teaching and learning methods (Skallerup Bessette 2014). One aim of this paper is to once again call on institutions to re-organize their resources and teaching structures in order to take the extra burden off of already marginalized instructors through formal communities like the ones mentioned above (see Drane et al 2019, Glisson et al 2014, and hooks 19942003).…”
Section: Pedagogical Influencementioning
confidence: 99%
See 2 more Smart Citations
“…Though institutions at the department level offer formal and informal programs for the development of future faculty, many are purely focused on the development of specific skills like teaching or the development of teaching philosophy and portfolios ( Viall et al, 2008 ). Many students have shown that for BIPOC students, learning communities that address both the professional skill building as well as their unique experiences associated with their personal identity, can lead to higher retention rates ( Tull et al, 2012 ; Drane et al, 2019 ).…”
Section: Background and Relevant Literaturementioning
confidence: 99%